CN103818898B (2015)
The invention discloses a graphene hybrid material with a controllable appearance and a preparation and appearance control method thereof. According to the graphene hybrid material, the surface and edge of graphene are both connected with hydroxyl metalloporphyrin or phthalocyanine, the hydroxyl metalloporphyrin or phthalocyanine is connected onto the surface of the graphene in a plane-plane parallel manner through a covalent bond and is connected with the edge of the graphene in a edge-surface vertical manner. The prepared graphene hybrid material has a wrinkle, folding or curved appearance, and the flake appearance of the graphene can be recovered by adding dyhydroxy metalloporphyrin or dyhydroxy metal phthalocyanine, so that the appearance of the graphene hybrid material provided by the invention has extremely good controllability; the prepared graphene hybrid material has the advantages of good dispersibility and stability in an organic solvent, unique structure, controllable appearance, excellent photoel